Concurrent TERT promoter and BRAF V600E mutation in epithelioid glioblastoma and concomitant low‐grade astrocytoma. Issue 1 (15th June 2016) - Matsumura, Nozomi; Nakajima, Nozomi; Yamazaki, Tatsuya; Nagano, Takuro; Kagoshima, Kaie; Nobusawa, Sumihito; Ikota, Hayato; Yokoo, Hideaki
Abstract : Epithelioid glioblastoma (E‐GBM) is a rare variant of glioblastoma (GBM), characterized by epithelioid cells with eosinophilic round cytoplasm devoid of stellate cytoplasmic processes. A number of studies have demonstrated that more than half of E‐GBMs harbor a valine to glutamic acid substitution at position 600 of the serine/threonine‐protein kinase BRAF ( BRAF V600E). However, there are no previous reports on E‐GBM with telomerase reverse transcriptase ( TERT ) promoter mutation in addition to BRAF V600E mutation. Here, we report an E‐GBM case in an 18‐year‐old man with BRAF V600E and TERT promoter mutations. The tumor composed of 80% E‐GBM and 20% diffuse astrocytoma‐like components, and BRAF V600E and TERT promoter mutations were detected in both. E‐GBM generally arises as a primary lesion; however, a few previous cases have been demonstrated to accompany low‐grade areas. Demonstration of concurrent BRAF V600E and TERT promoter mutations in low‐ and high‐grade lesions strongly suggested their identical origin, and acquisition of each mutation may be an early event, possibly playing a pivotal role in the genesis and subsequent progression to E‐GBM.